DIVISION III: COMMISSION 15: PHYSICAL STUDIES OF COMETS AND MINOR PLANETS. (13th August 2015) - Bockelée-Morvan, Dominique; Gil-Hutton, Ricardo; Cellino, Alberto; Hestroffer, Daniel; Belskaya, Irina N.; Davidsson, Björn J.R.; Dotto, Elisabetta; Fitzsimmons, Alan; Hestroffer, Daniel; Kawakita, Hideyo; Mothe-Diniz, Thais; Licandro, Javier; et al.
Abstract : The business meeting of IAU Commission 15 (C15) took place in Beijing on 29 August 2012, from 14:00 to 18:00, in room 405 of the China National Convention Center. This report of the business meeting of Commission 15 at the 2012 IAU GA is based on the report provided by Alberto Cellino, past president, and on the minutes taken by Daniel Hestroffer, secretary of Commission 15 in the triennium 2009 to 2012, and current secretary.